Auditory Intellectually Repetition (AIR) Learning Model as an Effort to Improve Students' Critical Thinking Skills in Physics Learning - Ariyani, Mila; Jumini, Sri (Universitas Sebelas Maret, 2025)
This study aims to provide students with an understanding of the implementation of the Auditory Intellectually Repetition (AIR) learning model as an effort to improve students' critical thinking skills in physics learning. Critical thinking skills are important components that students must have to explore complex physics concepts. Using the literature review method, this study analyzes various studies and literature related to the effectiveness of the AIR model in improving students' critical thinking skills. The AIR model, which combines aspects of auditory, intellectual, and repetition, functions to help students understand concepts more deeply through a structured process. This model provides students not only to receive information, but also to analyze, evaluate, and integrate new knowledge, so that they are able to make them more critical in understanding and solving physics problems. Understanding the implementation of this AIR model is expected to help students, especially prospective educators, in developing physics learning strategies that can improve students' critical thinking skills effectively.